2013
DOI: 10.1063/1.4773020
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous length dependence of the conductance of graphene nanoribbons with zigzag edges

Abstract: Charge transport through two sets of symmetric graphene nanoribbons with zigzag shaped edges in a two-terminal device has been investigated, using density functional theory combined with the nonequilibrium Green's function method. The conductance has been explored as a function of nanoribbon length, bias voltage, and the strength of terminal coupling. The set of narrower nanoribbons, in the form of thiolated linear acenes, shows an anomalous length dependence of the conductance, which at first exhibits a drop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[17][18][19][20] There are extensive reports on the transport properties of molecular junctions, carbon nanotubes, semiconductor nanowires and graphene. [21][22][23][24][25][26] Comparing to the large amount of experimental studies on the transport behavior of ZnO nanostructures, only a few theoretical reports have been found in recent years. Yang et al 27 observed clearly rectifying current-voltage characteristics in ZnO nanowires coupled by aluminum electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] There are extensive reports on the transport properties of molecular junctions, carbon nanotubes, semiconductor nanowires and graphene. [21][22][23][24][25][26] Comparing to the large amount of experimental studies on the transport behavior of ZnO nanostructures, only a few theoretical reports have been found in recent years. Yang et al 27 observed clearly rectifying current-voltage characteristics in ZnO nanowires coupled by aluminum electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to two additional possibilities: pyrene-1,2,6,7-tetrathiol (PTT) and 2,3,7,8-PTT. Other combinations, such as 1,3,6,8-PTT, are not considered because the additional separation between the thiols would make double attachment to the terminals impossible, while 3,4,8,9-PTT has been treated elsewhere [21] very recently.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the occupied peak just below the Fermi level in the 1,2,6,7-PTT transmission spectrum is substantially amplified, resulting in a higher low bias conductance than any of the PDT isomers. However, as in the case of 3,4,8,9-PTT [21], the benefits of the reduced contact resistance are rather limited, because the two thiol groups at each terminal are connected to the same C ring. This is a poor design since it does not qualitatively change the charge flow pathway.…”
Section: Resultsmentioning
confidence: 99%